Insights into Muscle Degeneration from Heritable Inclusion Body Myopathies - Krause, Sabine (Frontiers in Aging Neuroscience, 2015)
Muscle mass and function is gradually lost in age-related, degenerative neuromuscular disorders which also reflect the clinical hallmarks of sarcopenia. The consensus definition of sarcopenia includes a condition of age-related loss of muscle mass, quality and strength. The most common acquired muscle disease affecting adults aged over 50 years is sporadic inclusion body myositis (sIBM). Besides inflammatory effects and immune-mediated muscle injury, degenerative myofiber changes are characteristic features of the disease. Although the earliest triggering events in sIBM remain elusive, a plethora of downstream mechanisms are implicated in the pathophysiology of muscle wasting. Although it remains controversial whether hereditary forms of inclusion body myopathy (IBM) may be considered as degenerative sIBM disease models, partial pathophysiological aspects can mimic the much more frequent sporadic condition, in particular the occurrence of inclusion bodies in skeletal muscle. Various clinical aspects in genetically determined skeletal muscle disorders reflect age-related alterations observed in sarcopenia. Several intriguing clues from monogenic defects in heritable IBMs contributing to the molecular basis of muscle loss will be discussed with special emphasis on IBMPFD (inclusion body myopathy with Paget’s disease of bone and frontotemporal dementia) and GNE myopathy. Finally, also the recently identified dominant multisystem proteinopathy will be considered which may rarely present as inclusion body myopathy.